Antireflux covered metal stent for nonresectable distal malignant biliary obstruction: Multicenter randomized controlled trial. Issue 5 (7th May 2019) - Hamada, Tsuyoshi; Isayama, Hiroyuki; Nakai, Yousuke; Iwashita, Takuji; Ito, Yukiko; Mukai, Tsuyoshi; Yagioka, Hiroshi; Saito, Tomotaka; Togawa, Osamu; Ryozawa, Shomei; Hirano, Kenji; Mizuno, Suguru; et al.
Abstract : Background and Aim: An antireflux metal stent (ARMS) for nonresectable distal malignant biliary obstruction (MBO) may prevent recurrent biliary obstruction (RBO) as a result of duodenobiliary reflux and prolong time to RBO (TRBO). Superiority of ARMS over conventional covered self‐expandable metal stents (SEMS) has not been fully examined. Methods: We conducted a multicenter randomized controlled trial to examine whether TRBO of an ARMS with a funnel‐shaped valve was longer than that of a covered SEMS in SEMS‐naïve patients. We enrolled 104 patients (52 patients per arm) at 11 hospitals in Japan. Secondary outcomes included causes of RBO, adverse events, and patient survival. Results: TRBO did not differ significantly between the ARMS and covered SEMS groups (median, 251 vs 351 days, respectively; P = 0.11). RBO as a result of biliary sludge or food impaction was observed in 13% and 9.8% of patients who received an ARMS and covered SEMS, respectively ( P = 0.83). ARMS was associated with a higher rate of stent migration compared with the covered SEMS (31% vs 12%, P = 0.038). Overall rates of adverse events were 20% and 18% in the ARMS and covered SEMS groups, respectively ( P = 0.97). No significant between‐group difference in patient survival was observed ( P = 0.26). Conclusions: The current ARMS was not associated with longer TRBO compared with the covered SEMS. Modifications including addition of an anti‐migration system are required to use the current ARMS as first‐line palliative treatment of distal MBO (UMIN‐CTR clinical trial registration number: UMIN000014784).